IMPLEMENTASI PENDIDIKAN POLITIK PADA KELOMPOK TUNAWISMA DI KOTA BANDAR LAMPUNG PADA PEMILU 2024 - Andhika Purbakala Rona; Tabah Maryanah; Hertanto (Journal Publicuho, 2024)
This research analyzes the effectiveness of the Bandar Lampung City General Election Commission (KPU) in increasing the political participation of marginalized groups, especially homeless people, by PKPU Mandate Number 10 of 2018. Homeless groups face various obstacles, such as a lack of legal identity, social stigma, and limited access to information. which makes it difficult for them to engage in the democratic process. Even though the KPU has implemented a political education program for vulnerable groups, this effort focuses more on people with disabilities, so that the needs of the homeless are neglected. This study uses a qualitative descriptive method with an inclusion-based political education approach. The research results show that low data collection and a lack of special programs for homeless people are the main obstacles to increasing their participation. The implications of this ineffectiveness include low levels of political participation for homeless people, continued marginalization, and inequality in a democratic system that includes the principle of inclusivity. Recommendations provided include collaboration between the KPU, Social Services, and civil society organizations to cover the needs of homeless people, the implementation of tailored political education programs, and facilitating the disclosure of identity documents.